IMPLEMENTASI KEBIJAKAN PROGRAM AKSEPTOR KB PRIA DI KABUPATEN SUMEDANG - deden haria garmana; Lovita Hendrawati; Neng Lina Puspitasari; Osa Nurfitria; Ratnengsih; Siti Anisa Apriliani (LPPM UNSAP & FISIP UNSAP, 2023)
The Family Planning Program is not a program run solely by the central government. In the current era of decentralization, the authority of the central government regarding family planning programs must be properly decentralized, as stated in article (23) paragraph (1) of Law Number 52 of 2009 concerning Population Development and Family Development which reads,